Room on the broom - Donaldson, Julia; Scheffler, Axel (London : Macmillan, 2001)
A witch finds room on her broom for all the animals that ask for a ride, and they repay her kindness by rescuing her from a dragon.
3.7
K-3
Keywords: Animals -- Fiction; Dragons -- Fiction; Stories in rhyme; Witches -- Fiction; Animals -- Fiction; Dragons -- Fiction; Stories in rhyme; Witches -- Fiction